MATERI DAKWAH DALAM AL-QUR'AN DAN HADIS - Mistarija Mistarija (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Da’wah materials are subtances, content, ideas, opinions, teachings which will be presented to the people. According to the letter of Ali Imran (104), the materials da’wah are Al-khair Islamiyah and al-ma'ruf , thats the universal values contained in the Qur'an and the Hadith as well as everything good in a society which is in line with Al-khair. Aspects contained in these values include aqidah-tauhid, the shari'ah, and character-Sufism. Meanwhile, according to al-Qur'an Surat an-Nahl (125) of da’wah material to be conveyed is Sabili rabbik, take the path of God. God's way is the din of Islam as a whole is the ultimate source or essence is the Qur'an and Sunnah. Thus the da’wah material was al-Islam that comes from al-Qur'an and Sunnah on various issues of human livelihoods and livelihood